Problem Based Learning Strategy on Critical Thinking Skills of Grade X Students in Economics Subject at SMAN 5 Pekanbaru - Siti Maulidiyah; RM Riadi; Mujiono Mujiono (Kamil : Journal of Education, 2026)
This study aims to determine the effectiveness of the Problem Based Learning (PBL) strategy on students’ critical thinking skills in economics learning at SMAN 5 Pekanbaru. This research used a quantitative approach with a quasi-experimental method, with class X5 as the control group and X6 as the experimental group. Data were collected through pretest, posttest, and analyzed using statistical tests. The results showed that the implementation of PBL had a significant effect on improving students’ critical thinking skills, where the experimental class showed higher improvement than the control class. This indicates that PBL encourages students to actively analyze and solve problems. Therefore, the Problem Based Learning strategy is effective in enhancing students’ critical thinking skills.